(untitled) (Revista Venezolana de Salud Pública, 2018)
Descriptive study was conducted, using the rapid coverage monitoring, the population was equal to the sample with a total of 312 households, housing is considered effective those which determined the presence of children under 6 years. The technique for data collection was interview guided by a questionnaire, and found the following results of coverage: 88,46% for BCG, hepatitis B 73,07% for the RN, 26,92% polio, rotavirus 53,84%, 38,46% pentavalent, 40 antiinfluenza%, 56% and 40% viral trivalent for fever; these results being lower than those reported for the Lara state until August 2012. Of all children none met the national vaccination program and studied children 2-5 years of age was found 84,6% susceptible to vaccine-preventable diseases, being 77,53% and 56,18 for antiinfluenza for rotavirus. The predominant cause of failure was "no vaccine the day he played" 47,7% followed by "did not know I had to put" 35,77%, only 0,91% reported "medical contraindication. The importance of this research is to make known to the Epidemiology of Iribarren, outpatient and community community council "San Francisco II North", the results of coverage, performance, and reason for failure susceptibility, with the aim of reducing the susceptible population and thus achieve the reduction of morbidity and mortality for vaccine-preventable diseases and the economic impact that these conditions imply, through vaccination.